2017
DOI: 10.1377/hlthaff.2016.0626
|View full text |Cite
|
Sign up to set email alerts
|

ACOs Serving High Proportions Of Racial And Ethnic Minorities Lag In Quality Performance

Abstract: Accountable care organizations (ACOs) are intended, in part, to improve health care quality. However, little is known about how such reforms may affect disparities or how providers serving disadvantaged patients perform under Medicare ACO contracts. We analyzed racial and ethnic disparities in health care outcomes among ACOs—the relationship between the share of an ACO’s patients that are racial and ethnic minorities and the ACO’s performance. Using data from Medicare and from a national survey of ACOs, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…For example, there are racial and ethnic disparities in the use of electronic patient portals, 22 and accountable care organizations with higher proportions of racial and ethnic minorities appear to have poorer track records in achieving quality targets. 23 This could lead to de-implementation strategies exacerbating-not attenuating-disparities in overuse. But researchers can anticipate and measure this, and seek ways to address it, such as building in strategies to expand use of an electronic patient portal among patients from racial and ethnic subgroups, or to ensure equitable distribution of patients across accountable care organizations.…”
Section: Testing De-implementation Strategies That May Mitigate Biasmentioning
confidence: 99%
“…For example, there are racial and ethnic disparities in the use of electronic patient portals, 22 and accountable care organizations with higher proportions of racial and ethnic minorities appear to have poorer track records in achieving quality targets. 23 This could lead to de-implementation strategies exacerbating-not attenuating-disparities in overuse. But researchers can anticipate and measure this, and seek ways to address it, such as building in strategies to expand use of an electronic patient portal among patients from racial and ethnic subgroups, or to ensure equitable distribution of patients across accountable care organizations.…”
Section: Testing De-implementation Strategies That May Mitigate Biasmentioning
confidence: 99%
“…ACOs will face the same challenges as any P4P program, dealing with the same issues of already poorer quality in low-income and minority populations. 13 This race-and income-based differential access to the care coordination provided by ACOs with better resources could potentially exacerbate disparities in certain parts of the country. In a private insurance ACO, a greater increase in process measures was found among lowincome versus higher-income groups, with no significant difference in outcome measures.…”
Section: Acomentioning
confidence: 99%
“…Since the beginning of the program, the number of ACOs operating in rural America has increased considerably . As CMS releases ACO performance data, it is critical to evaluate how rural ACOs’ performance compares to that of urban ACOs and what organizational attributes are associated with ACO performance to inform policy and practice . This paper contributes such knowledge by evaluating associations between geographic, structural, and service‐provision attributes of MSSP ACOs and the ACOs’ quality performance.…”
mentioning
confidence: 99%
“…Yet, to date, only a few studies have explored factors associated with MSSP ACOs’ quality performance. Research has shown that ACOs serving higher proportions of minorities had poorer performance on 25 of the 36 individual or composite quality measures during their first performance year . Several qualitative studies dived into ACO‐level factors and strategies that might contribute to high performance on cost savings and quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation